Democracy in Uruguay: Body education and leisure in the “New Model of Physical Education” (1985-1990) - Seré Quintero, Cecilia; Fernandez Vaz, Alexandre (Education Policy Analysis Archives, 2016)
This article revisits formal Physical Education programs in the democratization process after the last civic-military dictatorship in Uruguay (1973-1985). We explore the “New Model of Physical Education” proposed by the National Commission of Physical Education in 1986 and at the same time the relation between body and modern politics. Studying recreational programs between 1985 and 1990 we observe that leisure time was saw as a strategy in favor of workers recovery. In addition we found that public policies that attempted to manage population's free time were guided by an interest in educate for the good use of leisure time and by hobbies promotion as a way to spend the not labor time.